2012
DOI: 10.1007/s00253-012-4529-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth condition optimization for docosahexaenoic acid (DHA) production by Moritella marina MP-1

Abstract: The marine organism Moritella marina MP-1 produces the polyunsaturated fatty acid docosahexaenoic acid (DHA). While the basic metabolic pathway for DHA production in this organism has been identified, the impact of growth conditions on DHA production is largely unknown. This study examines the effect of supplemental carbon, nitrogen and salts, growth temperature and media composition and pH on DHA and biomass production and the fatty acid profile. The addition of supplemental nitrogen significantly increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This phenomenon was also found in other microorganisms. , For example, Patil and Gogate found the DCW and lipid of Schizochytrium limacinum SR21 was decreased, when the initial yeast extract content was above 10 g/L. However, similar to other microorganisms accumulating lipid such as Isochrysis zhangjiangensis and Moritella marina MP-1 which grew slowly under the condition of nitrogen limitation, the changes in terms of DCW and lipid productivity were small in C. cohnii M-1-2, , so a suitable nitrogen feeding strategy is necessary for high lipid productivity.…”
Section: Results and Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This phenomenon was also found in other microorganisms. , For example, Patil and Gogate found the DCW and lipid of Schizochytrium limacinum SR21 was decreased, when the initial yeast extract content was above 10 g/L. However, similar to other microorganisms accumulating lipid such as Isochrysis zhangjiangensis and Moritella marina MP-1 which grew slowly under the condition of nitrogen limitation, the changes in terms of DCW and lipid productivity were small in C. cohnii M-1-2, , so a suitable nitrogen feeding strategy is necessary for high lipid productivity.…”
Section: Results and Discussionsupporting
confidence: 52%
“…It was reported that the initial nitrogen content has significant effects on growth and lipid accumulation in many microbes, such as Moritella marina MP-1 and Schizochytrium sp. S31. , Therefore, the effects of initial nitrogen concentration on the growth and DHA productivity of C. cohnii M-1-2 were investigated. In this study, nitrogen in the form of yeast extract was used.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aurantiochytrium (formerly known as the genus Schizochytrium) is a single cell Thraustochytrid well-known for its capacity to produce and accumulate large amounts of VLC-PUFAs in cellular lipids, especially DHA, whose content exceeds 25% of the dry cell weight (DCW) and whose biomass can reach 130–150 g/L. , Thus, Aurantiochytrium has been established as a candidate for commercial production of PUFAs. , Different from the conventional combination of fatty acid elongation and an aerobic desaturation system, Aurantiochytrium synthesizes PUFAs de novo through a polyketide synthase (PKS) system, which has prominent advantages, including less NADPH need and a simpler fatty acid profile . Many bacteria also synthesize PUFAs through the PKS system, such as Shewanella oneidensis, Colwellia psychrerythraea, Moritella marina, and Aureispira marina . However, the control mechanism for the carbon chain length in PKS is still a mystery. , Orikasa et al cloned all PKS genes for DHA biosynthesis in M.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Different from the conventional combination of fatty acid elongation and an aerobic desaturation system, Aurantiochytrium synthesizes PUFAs de novo through a polyketide synthase (PKS) system, which has prominent advantages, including less NADPH need and a simpler fatty acid profile. 11 Many bacteria also synthesize PUFAs through the PKS system, such as Shewanella oneidensis, 12 Colwellia psychrerythraea, 13 Moritella marina, 14 and Aureispira marina. 15 However, the control mechanism for the carbon chain length in PKS is still a mystery.…”
Section: ■ Introductionmentioning
confidence: 99%